1967
DOI: 10.1590/s0006-87051967000100009
|View full text |Cite
|
Sign up to set email alerts
|

Observações sôbre o efeito da luz no crescimento da tiririca, Cyperus rotundus L.

Abstract: SINOPSEForam estudados: os efeitos do sombreamento de tiririca (Cyperus rotundus L.), no campo, com plantas de Canavalia ensiformis D.C.; a ação de luz artificial; o ponto de compensação de luz. o sombreamento reduziu drasticamente a multiplicação dos tubérculos. Plantas mantidas com luminosidade artificial de 15% da radiação solar tiveram o desenvolvimento subterrâneo muito prejudicado. A capacidade vegetativa da tiririca mostrou-se reprimida sòmente com redução acentuada da luminosidade. -INTRODUÇÃOApesar da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1973
1973
1997
1997

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Magalhaes (14) reported that shading with varying thicknesses of cotton cloth to produce shades of 85 and 92.5% of full sun reduced the growth and tuber formation by approximately 60% in Brazil. Hauser (9) also reported a 10 to 57% reduction in the number of tubers and basal bulbs that were formed when shaded with a plastic screen which gave 72% shade.…”
Section: Volume 23 Issue 4 (July) 1975mentioning
confidence: 99%
See 1 more Smart Citation
“…Magalhaes (14) reported that shading with varying thicknesses of cotton cloth to produce shades of 85 and 92.5% of full sun reduced the growth and tuber formation by approximately 60% in Brazil. Hauser (9) also reported a 10 to 57% reduction in the number of tubers and basal bulbs that were formed when shaded with a plastic screen which gave 72% shade.…”
Section: Volume 23 Issue 4 (July) 1975mentioning
confidence: 99%
“…These experiments revealed many cropping practices which can be managed to decrease the competitive growth of nutsedge and favor crop develop ment. For example, several competitive cover crops (14) and a few commercial crops such as sweet potato [Ipomea batatas (L.) Lam.] (8) have effectively reduced the population of nutsedge in heavily infested fields.…”
Section: Competitive Cropping Practicesmentioning
confidence: 99%